USE OF PREDICTIVE EL-GANZOURI SCORE IN EVALUATION OF DIFFICULT AIRWAY IN OBESE PATIENTS - A. A. Klimov; A. A. Mаlаkhovа; S. А. Kаmnev; V. V. Subbotin (Вестник анестезиологии и реаниматологии)
The frequency of difficult laryngoscopy and tracheal intubation in obese patients is higher compared to non-obese patients. Therefore it is important to perform an adequate assessment of airway before surgery with general anesthesia and tracheal intubation in such patients. This retrospective study evaluated the predictive value of El-Ganzouri score in the patients with body weight index exceeding 30 kg/sq. m.Subjects and methods. 116 patients were enrolled into the study, general anesthesia with tracheal intubation was planned in all those patients. The airway of all patients was assessed by El-Ganzouri score prior to surgery. Regardless of the number of scores in a patient, a video laryngoscope was always used, however by the first intubation attempt it was used as a regular one.Results. The score sensitivity made 0.81, specificity – 0.66, positive predictability – 0.4, negative predictability – 0.93. The area under ROC-curve made 0.82.Conclusions. We recommend El-Ganzouri score for evaluation of airway in the patients with BMI exceeding 30 kg/sq. m. since it possesses good modeling properties (AUC = 0.85) and allows selecting the safest way of intubation.